Efektivitas Penerapan UU No. 4 Tahun 2023 Tentang Pengembangan Dan Penguatan Sektor Keuangan Pada Kasus Gagal Bayar Asuransi Usaha Bersama - Ginintu, Mohamad Irvan Fahrizal; Kasim, Nur Mohamad; Mandjo, Julius T. (CV. ITTC INDONESIA, 2023)
Law Number 4 of 2023 as a legal framework designed to regulate and strengthen the financial sector. The purpose of this writing is to examine the Effectiveness of the Implementation of Law Number. 4 of 2023 concerning Development and Strengthening of the Financial Sector in Cases of Default in Joint Business Insurance. The research method using this type of research is normative juridical and uses secondary data sources obtained from the results of a literature review or other literature related to the research problem. The powers given to financial supervisory authorities will strengthen oversight of insurance company practices and prevent the risk of default. This Act also promotes transparency and better financial reporting of insurance companies. Disclosure of clearer and more accurate financial information, as well as an independent audit, will help increase the understanding and trust of customers and supervisory authorities in the financial condition of insurance companies.